2022
DOI: 10.1055/s-0042-1755311
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Vitamin B12 Levels and Smell Affection in COVID-19 Patients

Abstract: Introduction Olfactory and gustative alterations are frequent in the initial stages of the COVID-19 infection. Vitamin B12 deficiency has been linked to olfactory dysfunction. Objective The present study aimed to assess the relationship between vitamin B12 levels and smell affection in COVID-19 patients. Methods The present study included 201 laboratory-confirmed COVID-19 patients. Smell affection was assessed using self-rated olfactory function. Serum vitamin B12 levels were assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…In our study, when the value of the vitamin B12 variable decreases, the risk of COVID-19 increases. Although non-explained the mechanism of the relationship between vitamin B12 and COVID-19 fully, there are some studies that emphasized vitamin B12 supplementation reduces the symptoms caused by COVID-19 in the literature [22] [23] . In addition, when serum vitamin B12 is below 222.5 ng/L it may increase the risk of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, when the value of the vitamin B12 variable decreases, the risk of COVID-19 increases. Although non-explained the mechanism of the relationship between vitamin B12 and COVID-19 fully, there are some studies that emphasized vitamin B12 supplementation reduces the symptoms caused by COVID-19 in the literature [22] [23] . In addition, when serum vitamin B12 is below 222.5 ng/L it may increase the risk of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that surviving COVID-19 infected individuals had higher levels of vitamin B12 compared to those who died from the virus 36 . Lower vitamin B12 also seems to be related to smell affection in COVID-19 patients 37 . According to a recent transcriptome analysis, vitamin B12 blocks several inflammation-related pathways that are activated in patients with moderate or severe COVID-19 infection 38 .…”
Section: Introductionmentioning
confidence: 89%
“…The studies found out that this combination enhances protein and nucleic acid formation as well as inhibits metabolism and activity of immune cells. Thus, the immune response improved drastically (29).…”
Section: Vitamin B12mentioning
confidence: 99%